Effect of time of harvest at different moisture contents on physiological and storability attributes of pigeon pea (Cajanus cajan) - Olufelo Olusola; Sharon Ifechi; Ukabiala Ekeoma (Innovations in Agriculture, 2023)
The physical quality and physiological performance of seeds can be influenced by numerous factors, including the moisture content at harvest and drying temperature. This study evaluated the effect of time of harvest at different moisture contents on physiological attributes and storability potential of pigeon pea in the tropics. The ten pigeon pea genotypes used for the experiment were sourced from International Institute of Tropical Agriculture (IITA) Ibadan, Oyo State, Nigeria. The field experiment was a Randomized Completely Block Design (RCBD) with three replications. The seeds were harvested at maturity on the field at 12, 15 and 17 % moisture content. Harvested seeds from each treatment were divided into three seed lots of 400g each with three (3) replicate each. Packaged seed lots of each treatment were stored under ambient environment. The temperature and relative humidity of the seed stores were monitored and maintained daily using hygrometers. Seed samples were taken from each packaged seed lot for evaluation at 30-days interval for a period of 240 days. The following physiological attributes were evaluated-;Standard germination, Seedling Vigor Index, Acceleration ageing and mean Germination index. Data collected from the above experiment on different characters were subjected to analysis of variance. The study concludes that the anticipation of harvest and drying seed at moisture content above 12 and 15 % in pigeon pea on the field resulted in low and poor physiological performance. Also, pigeon pea harvested with higher moisture (17%) are more susceptible to damage which cause lower viability and seedling vigour with corresponding higher mean germination time. The study showed that, best results across the evaluated attributes during the time of storage were associated with genotypes with the lowest and moderate percentage of moisture at harvest. Therefore, for better physiological performance, optimal harvest timing for pigeon pea seeds should be at 12 to 15% range of moisture content but preferably, 15% in other to reduce the rate of seed scattering and wastages through pod dehiscence.